A method for analyzing heavy metal occupation sites of fayalite phase in smelting slag
By simulating the sludge formation process and multiple characterization methods combined with DFT calculation, the binding state and occupancy site of Cu, Pb, and As in iron olivine are clarified, the problem of heavy metal occupying iron olivine sites in sludge is solved, and more effective sludge treatment technology is provided.
Patent Information
- Application Number
- CN202210161822.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-22
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-02-22
AI Technical Summary
Heavy metals in the smelting slag occupy the iron olivine site, resulting in harmlessness and resource processing of secondary metals, and the mechanism of action between different types or valence heavy metals and iron olivine is unclear.
By simulating the sludge formation process, combining multiple characterization methods and DFT calculations, the binding state and occupancy sites of Cu, Pb, and As in the iron olivine structure are clarified. The specific steps include preparing Fe2SiO4 and M-Fe2SiO4 powders, performing XRD, FT-IR, Raman and XPS analysis, and determining the occupancy site of the heavy metal through DFT calculations.
The distribution and lattice replacement rules of Cu, Pb, and As in iron olivine were successfully analyzed, and the different positions of different heavy metals in iron olivine were clearly defined, providing a more effective research basis for harmless and resource-based disposal of smelt slags.
Smart Images

Figure CN115128110B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of harmless treatment and resource utilization of metallurgical and bulk industrial smelting slag waste, and specifically relates to a method for analyzing heavy metal occupation sites of fayalite phase in smelting slag. Background Art
[0002] Fayalite has a stable spinel structure and can bind valuable / harmful metals. It is widely found in nonferrous metal smelting slags such as copper smelting slag, lead smelting slag and nickel smelting slag. The valuable / harmful metal elements in smelting slag are characterized by large content and a wide variety, and have both environmental and resource attributes. However, since heavy metals will occupy the fayalite site during the smelting process and form a dense inclusion state with fayalite, the harmlessness and resource utilization of secondary metals are severely restricted. At the same time, the complex composition of smelting slag makes the interaction mechanism between heavy metals of different types or different valence states and fayalite and their occupation sites in fayalite unclear, making the rational treatment and disposal of smelting slag face huge challenges.
[0003] Existing technologies have analyzed the occupied sites of Zn in fayalite, but there is no systematic research report on the binding relationship of M-Fe2SiO4 (M=Cu, As and Pb) in fayalite-rich smelting slag. In order to clarify the binding state and occupied sites of heavy metals (Cu, Pb, As) in fayalite, an effective method must be developed to understand the interaction mechanism between fayalite and heavy metals during the formation of smelting slag, and provide a research basis for the development of more effective and greener smelting slag harmless and resource-based disposal technologies. Summary of the invention
[0004] In view of the above problems, the present invention discloses a method for analyzing the occupation sites of heavy metals in the fayalite phase in smelting slag. By simulating the formation process of smelting slag and combining a variety of characterization methods and DFT calculations, the binding state and occupation sites of Cu, Pb and As in the fayalite structure are clarified.
[0005] The purpose of the present invention is achieved through the following technical solutions:
[0006] A method for analyzing heavy metal occupation sites of fayalite phase in smelting slag comprises the following steps:
[0007] (1) mixing silicon dioxide, ferrosoferric oxide and ferrous sulfide, mixing by ball milling, smelting, cooling and ball milling to obtain Fe2SiO4 powder;
[0008] (2) mixing Fe2SiO4 powder with metal oxides, mixing by ball milling, smelting, cooling, crushing, and ball milling to obtain heavy metal-containing fayalite powder M-Fe2SiO4;
[0009] (3) XRD analysis and FT-IR analysis of Fe2SiO4 and M-Fe2SiO4;
[0010] (4) Fe2SiO4 and M-Fe2SiO4 were subjected to Raman analysis and XPS analysis.
[0011] Preferably, the metal oxide in step (2) is one or more of copper oxide, lead oxide, arsenic trioxide, and zinc oxide, and the M-Fe2SiO4 is one or more of Cu-Fe2SiO4, Pb-Fe2SiO4, As-Fe2SiO4, and Zn-Fe2SiO4.
[0012] Preferably, the mass ratio of silicon dioxide:ferrosoferric oxide:ferrous sulfide in step (1) is (7-10):(4-8):(4-8), the mass of Fe2SiO4 powder in step (2) is 10-20g, and the amount of metal oxide added is 0-15wt% of Fe2SiO4.
[0013] Preferably, the mass ratio of silicon dioxide:ferrosoferric oxide:ferrous sulfide in step (1) is 7:4:4, the mass of Fe2SiO4 powder in step (2) is 15g, and the amount of metal oxide added is 3.2-11.8wt% of Fe2SiO4.
[0014] Preferably, the ball milling mixing and ball milling conditions in step (1) and step (2) are: ball milling time is 5 to 10 minutes, and the ball milling speed is 400±100 rpm.
[0015] Preferably, the particle size of the Fe2SiO4 powder in step (1) and the M-Fe2SiO4 powder in step (2) are both 50-80 mesh.
[0016] Preferably, the smelting conditions in step (1) and step (2) are: vacuum degree of -0.05 to -0.1 MPa, power of 1200 to 1500 W, temperature of 1300 to 1400 ° C, time of 10 to 15 min, and natural cooling for 24 to 36 h.
[0017] Preferably, the XRD scanning angle in step (3) is 20° to 60°, and the FT-IR analysis spectrum range is 1000-400cm -1 .
[0018] Preferably, after step (4), DFT calculation is further performed to calculate the occupied sites of heavy metals and fayalite, and the DFT calculation method is: spin-polarized density functional theory calculation is performed using the Hubbard U (DFT+U) correction implemented in the Vienna ab initio Simulation Package, the generalized gradient approximation of Perdew-Burke-Ernzerh is used for electron exchange calculation, the pseudopotential uses a plane wave pseudopotential with a kinetic energy cutoff energy of 400 eV in the projected enhanced wave PAW method, and in order to better describe the electrons of Fe 3d, the Hubbard effective U value is set to 3.6 eV, and the energy convergence criterion is set to 10 -5 eV, and continue to optimize the atomic positions until the Hermann-Feynman force on each atom is less than The Brillouin zone is sampled using a 7 × 3 × 5 k-point grid in the Monkhorst-Pack setup.
[0019] Preferably, the XRD analysis in step (2) analyzes the binding relationship between Fe2SiO4 and heavy metals, and the FT-IR analysis analyzes the changes in chemical bonds in Fe2SiO4 and M-Fe2SiO4; and the Raman analysis and XPS analysis in step (3) determine the occupancy rules of heavy metals in Fe2SiO4.
[0020] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0021] (1) The present invention simulates the formation process of smelting slag and can successfully synthesize fayalite containing heavy metals (Cu, Pb, As) in 10 minutes.
[0022] (2) The problem of large interference from actual smelting slag and difficulty in identification and characterization was solved, and the distribution and lattice substitution rules of Cu, Pb, and As in fayalite were clarified.
[0023] (3) It was found that different heavy metals occupy different positions in fayalite. Taking Cu(II), Pb(II), and As(III) as examples, divalent metals such as Cu(II) and Pb(II) will replace the M2 position of Fe(II), and As(III) will replace the M2 position of Fe(II) and some central Si atom positions. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A flow chart of a method for analyzing heavy metal occupancy sites of fayalite phase in smelting slag provided by the present invention.
[0025] Figure 2 These are the XRD patterns of the samples synthesized from fayalite and different heavy metals Cu (a, b), Pb (c, d) and As (e, f) in Example 2.
[0026] Figure 3 FT-IR images (a, b, c) and Raman spectra (d, e, f) of fayalite in Example 3 when Cu, Pb and As are combined respectively.
[0027] Figure 4 These are the XPS graphs of the Si 2p orbitals (a, b, c) and O1s orbitals (d, e, f) of Cu-Fe2SiO4, Pb-Fe2SiO4, and As-Fe2SiO4 in Example 4.
[0028] Figure 5 Detailed XPS chemical bond distribution diagram of Si 2p orbital (a) and O1s orbital (b) of Fe2SiO4, 11.8% Cu-Fe2SiO4, 11.8% Pb-Fe2SiO4 and 11.8% As-Fe2SiO4 in Example 4.
[0029] Figure 6 Figure 5 is a diagram of the M1 and M2 sites in the unit cell structure of fayalite in Example 5 (a), the corresponding configuration diagram of Fe2SiO4 with Pb, Cu and As substituted at the M1 and M2 sites respectively (b), and the charge-compensated structure diagram of Fe2SiO4 with As substituted at the M1 and M2 sites (c). In 6(b), gray is Pb, orange is Cu, and bright purple is As. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto. For process parameters not particularly noted, conventional techniques may be used.
[0031] Example 1
[0032] Silicon dioxide, ferroferric oxide and ferrous sulfide are selected as the raw materials for synthesizing fayalite. Weigh 7g of silicon dioxide, 4g of ferroferric oxide and 4g of ferrous sulfide and mix them. In order to mix them thoroughly, the mixed raw materials are ball-milled for 5 minutes using a ball mill. Then the ball-milled raw materials are placed in a smelting furnace of model LH-15A (Dongguan Lihua Machinery Equipment Co., Ltd.) for vacuum smelting. The smelting conditions are vacuum degree -0.1Mpa, power 1200w, temperature control at 1300-1400℃, smelting time is 10min, and then naturally cooled for 24 hours. After the cooled sample is crushed, it is ball-milled into powder again (passed through a 50-80 mesh sieve) for standby use. The ball milling time is 5min. The powder is Fe2SiO4. The lattice constant of the newly synthesized Fe2SiO4 Very close to the lattice constant of Fe2SiO4 in the Crystallographic Open Database The results reported in the literature (Dyar MD, Sklute EC, Menzies ON, et al. Spectroscopic characteristics of synthetic olivine: an integrated multi-wavelength and multi-technique approach [J]. American Mineralogist, 2009, 94 (7): 883-898.).
[0033] The synthesis method of the copper-containing iron olivine (Cu-Fe2SiO4) sample, the lead-containing iron olivine (Pb-Fe2SiO4) sample, and the arsenic-containing iron olivine sample (As-Fe2SiO4) is consistent with the synthesis method of iron olivine. In brief, as shown in Table 1, different amounts of metal oxides (copper oxide, yellow lead oxide, and arsenic trioxide) were ball-milled with 7g of silicon dioxide, 4g of ferroferric oxide, and 4g of ferrous sulfide for 5 minutes, and then the ball-milled raw materials were placed in a smelting furnace in a vacuum state for smelting. The smelting conditions were vacuum degree -0.1Mpa, power 1200w, temperature controlled at 1300-1400℃, smelting time of 10min, and then naturally cooled for 24 hours. After the cooled sample was crushed, it was ball-milled into powder (passed through a 50-80 mesh sieve) again for standby use. The ball-milling time was 5min, and the powder was M-Fe2SiO4 (Cu, Pb, As).
[0034] Table 1 Mass of main raw materials for synthesizing M-Fe2SiO4 in Example 1
[0035]
[0036] Example 2
[0037] XRD was used to characterize the binding relationship between fayalite and heavy metals. Figure 2 shown. Figure 2 It can be seen that the newly synthesized Fe2SiO4 material matches well with the standard peak diffraction pattern of fayalite (JCPDS 01-076-0852), and the peak intensity indicates that fayalite has good crystallinity after smelting, and the addition of metal oxides (copper oxide, yellow lead oxide and arsenic trioxide) will not affect the crystallinity of fayalite. Figure 2 No peaks corresponding to CuO, PbO and As2O3 were found in (a, c, e), which means that the above metal ions enter the fayalite structure and form M-Fe2SiO4 (Cu, Pb, As). Figure 2As shown in (b, d, f), the XRD diffraction angle is enlarged from 35° to 37°. Compared with the newly synthesized Fe2SiO4, the characteristic peaks of M-Fe2SiO4 (Cu, Pb, As) move to higher angles to varying degrees. The maximum shift angles of Cu-Fe2SiO4, Pb-Fe2SiO4 and As-Fe2SiO4 are 0.17°, 0.10° and 0.07°, respectively. The shift of the diffraction peaks of M-Fe2SiO4 (Cu, Pb, As) indicates that Cu(Ⅱ), Pb(Ⅱ) and As(Ⅲ) enter the Fe2SiO4 structure and replace Fe(II) to form M-Fe2SiO4 (Cu, Pb, As).
[0038] Example 3
[0039] The changes of the main chemical bonds in Fe2SiO4, Cu-Fe2SiO4, Pb-Fe2SiO4 and As-Fe2SiO4 were obtained by FT-IR. Figure 3 (a, b, c) are shown. In the FT-IR spectrum of Fe2SiO4, the -1 、912cm -1 and 871cm -1 The energy band at 826cm is attributed to the ν3 vibration mode of the [SiO4] tetrahedron, which is mainly caused by Si-O stretching vibration. -1 The energy band at 620cm is attributed to the ν1 vibration mode of the [SiO4] tetrahedron, while the -1 The nearby bands seem to be involved in the motion of the entire FeO6 octahedron. -1 、506cm -1 and 474cm -1 The energy band is caused by the ν4 vibration of the [SiO4] tetrahedron, which is mainly affected by the OO and Fe-O bands. Obviously, due to the participation of metal oxides in the reaction, the chemical bonds of Cu-Fe2SiO4, Pb-Fe2SiO4 and As-Fe2SiO4 have not changed significantly. Figure 3 As shown in (a), in the FT-IR spectrum of Cu-Fe2SiO4, the -1 A new energy band appeared at 794 cm-1, which may be attributed to the formation of Si-O-Fe-Cu chemical bonds in the Cu-Fe2SiO4 sample. With the addition of Cu ions, the intensity of the internal vibration bands ν1, ν3 and ν4 of Cu-Fe2SiO4 increased slightly, and the bands were located at 794 cm-1. -1 and 620cm -1 The chemical bonds at the Fe2SiO4 are gone. This means that the addition of Cu ions changes the internal structure of Fe2SiO4. Figure 3 (b) (Pb-Fe2SiO4) and Figure 3Similar results were also found in (c) (As-Fe2SiO4). The above results indicate that in the formation process of simulated copper smelting slag, metal ions such as Cu, Pb and As participate in the formation of Fe2SiO4 structure and change the lattice structure of Fe2SiO4.
[0040] like Figure 3 As shown in (d, e, f), the Raman spectra of Fe2SiO4 and M-Fe2SiO4 (Cu, Pb, As) further confirm the binding relationship between fayalite and heavy metals. The measured spectrum of the newly synthesized Fe2SiO4 is similar to the known Raman spectrum of fayalite ( Figure 3 (d)), the main peak is at 813 cm -1 , shoulder peak is at 838cm -1 , which belongs to the stretching vibration mode of SiO4 (ν1 and ν3). -1 The peak at 168 cm is attributed to the ν2 vibration of SiO4. -1 and 227cm -1 The peak at 284cm is attributed to the translational vibration mode of SiO4. -1 and 151cm -1 The peak at is located in the wave number region of the SiO4 vibration mode, and has strong characteristics of the rotation zone of the active site of Fe in fayalite (rotation mode of the M2 active site). However, with the addition of heavy metals, the vibration mode inside M-Fe2SiO4 (Cu, Pb, As) is opposite to the primary and secondary vibration modes of ν1 and ν3 in Fe2SiO4 ( Figure 3 (d), 3(e) and 3(f)). Figure 3 As shown in (d), the Raman spectrum of Cu-Fe2SiO4 is at 386 cm -1 and 468cm -1 A new peak appears at 284 cm, which is called the active stretching vibration peak (ν2) of SiO4. -1 and 151cm -1 The SiO4 vibration mode at the active site and the M2 translation mode in the active site of Fe have changed significantly. Figure 3 As shown in (e), Pb-Fe2SiO4 at 309cm -1 and 364cm -1 The two new peaks at are attributed to the SiO4 vibration mode and the M2 translation mode. The results show that during the formation of smelting slag, lead atoms and copper atoms act in a similar way to fayalite, entering the lattice structure of fayalite by replacing the M2 active sites of Fe in fayalite.
[0041] However, in Figure 3 In (c), as the As content increases, the peak at 813 cm -1 The characteristic peak intensity of ν1 vibration gradually increases, and the peak at 838cm -1 The intensity of the characteristic peak of the ν3 vibration mode at α is gradually decreasing, which is consistent with the Raman changes in Cu-Fe2SiO4 and Pb-Fe2SiO4. However, with the increase of As content, no relevant changes related to the active sites of Fe in fayalite were found. Figure 3 As shown in (f), at 838cm -1 and 813cm -1 The changes at this point were only found in As-Fe2SiO4.
[0042] Example 4
[0043] The surface composition and chemical state of M-Fe2SiO4 (Cu, Pb, As) were measured by detailed XPS. Figure 4 As shown in Figures 4(a), 4(b), and 4(c), with the addition of Cu, Pb, and As, the main features of Si 2p in M-Fe2SiO4(Cu, Pb, As) shift toward the low binding energy direction, with the maximum displacement of about 1.15 eV, 1.15 eV, and 1.18 eV. The detailed changes of Si 2p in the newly synthesized Fe2SiO4 and M-Fe2SiO4(Cu, Pb, As) are shown in Figures 4(a), 4(b), and 4(c). Figure 5 (a) As shown. There are two forms of Si in the newly synthesized Fe2SiO4, the high binding energy of 103.17eV is attributed to Si-O-Si, and the low binding energy of 101.38eV is attributed to Si-O-Fe, as shown in Table 2, accounting for 93.72% and 6.28% respectively. In addition to the above two peaks, a new peak is located between Si-O-Si and Si-O-Fe, which may be attributed to Si-OM (M = Cu, Pb and As). The above results show that heavy metals successfully enter the fayalite lattice.
[0044] Figure 4 (d), 4(e), and 4(f) show the O1s spectra of the newly synthesized fayalite and M-Fe2SiO4 (Cu, Pb, As). Similar to the Si 2p peak, the O 1s peak shifts toward the low binding energy direction by about 1.15 eV, 0.85 eV, and 0.94 eV after the addition of Cu, Pb, and As, respectively. The results show that the addition of heavy metals leads to an increase in the valence electron density around oxygen atoms. Figure 5As shown in (b), the newly synthesized Fe2SiO4 has two peaks at 532.33eV and 530.56eV, which can be attributed to Si-O-Si and Si-O-Fe. However, three equally abundant oxygen sites with different energies were found in M-Fe2SiO4 (Cu, Pb, As), which were attributed to the three chemical bonds of Si-O-Si, M(Cu, Pb, As)-O-Si and Fe-O-Si. Therefore, referring to the O1s spectrum that conforms to the three peaks with the same intensity (same region), the bridging oxygen in the Si-O-Si bond in the Cu-Fe2SiO4 sample is located at a high binding energy of about 533.20eV. The binding energy position of Fe-O-Si is considered to be Fe in Fe2SiO4 at the M1 site, with a binding energy of about 531.25eV, while the binding energy symbolizing Cu-O-Si is about 529.57eV, when Cu is at the M2 site of the two binding sites of Fe in Fe2SiO4. At the same time, Pb-O-Si and As-O-Si bonds were also found in Pb-Fe2SiO4 and As-Fe2SiO4, indicating that heavy metals are incorporated into the fayalite lattice by replacing the fayalite M2 site.
[0045] Table 2 Detailed XPS chemical bond energy distribution of Example 4
[0046]
[0047] Where BE is the binding energy and FWHM is the half-maximum width of the peak.
[0048] Example 5
[0049] In order to clarify the structure and difference of the three structures of fayalite theoretically, spin-polarized density functional theory calculations were performed for Cu-Fe2SiO4, Pb-Fe2SiO4 and As-Fe2SiO4 structures respectively using the Hubbard U (DFT+U) correction implemented in the Vienna ab initio Simulation Package. The generalized gradient approximation of Perdew-Burke-Ernzerh was used for electron exchange calculations, and the pseudopotential used was a plane wave pseudopotential with a kinetic energy cutoff of 400 eV in the projected augmented wave (PAW) method. In order to better describe the electrons of Fe 3d, the Hubbard effective U value was set to 3.6 eV and the energy convergence criterion was set to 10 -5 eV, and continue to optimize the atomic positions until the Hermann-Feynman force on each atom is less than The Brillouin zone is sampled using a 7 × 3 × 5 k-point grid in the Monkhorst-Pack setup.
[0050] like Figure 6As shown in (a), the unit cell structure of olivine silicate Fe2SiO4 shows that the Fe2SiO4 crystal has an orthorhombic structure, the space group is Pb nm, and its unit cell structure is composed of divalent metal cations (hexacoordinated Fe 2+ cation) linked [SiO4] 4- Tetrahedron composition. Figure 6 (a), Fe(II) has two types of sites in Fe2SiO4, M1 and M2. When the Fe(II) cation is located at the inversion symmetric position, it is denoted as M1 type (2Fe(M1)-O-SiO), and when the Fe(II) cation is located on the mirror symmetry plane, it is M2 type, denoted as SiO-2O-Fe(M2)-Fe(M2)-2O-SiO.
[0051] In order to clarify the theoretical process of heavy metal ion substitution mechanism in fayalite, we studied the structural changes of fayalite when the Fe(II) site (M1 or M2) was replaced by Cu(II), Pb(II) and As(III) respectively. The corresponding structural changes are shown in the figure Figure 6 (a) and Figure 6 As shown in (b), both M1 and M2 substitution modes belong to the orthorhombic phase, with the space group being Pbnm. The free energy changes of Cu(II) and Pb(II) replacing Fe(II) at the M2 position of Fe2SiO4 are -1.20 eV and -0.46 eV lower than the free energy changes of Cu(II) and Pb(II) replacing Fe(II) at the M1 position of Fe2SiO4, respectively, indicating that the M2 substitution mode is more favorable than the M1 substitution mode. Figure 6 (b) The DFT calculation results show that for the high-valent cation As(III), the binding ability of As(III) at the M1 position is stronger than that of As(III) at the M2 position, indicating that As(III) replaces the M1 site of fayalite. However, the above results are inconsistent with the results of Raman, XPS, etc. Therefore, we consider the charge compensation after Fe(II) is replaced by As(III). In addition to the sites where As(III) replaces Fe(II) at M1 or M2, other As(III) can also replace Si atoms for charge compensation. According to this theory, the calculation is as follows: Figure 6 (c) Fe2As substituted by As(III) at the M2 position x Si 1-x The free energy change of O4 (-2.53 eV) is lower than that of Fe2As substituted by As(III) at the M1 position. x Si 1-xThe free energy of O4 changes, which indicates that in the olivine structure of As-Fe2SiO4, As(III) simultaneously replaces Fe(II) and part of Si atoms in the M2 site. This also explains why there are significant differences between Cu-Fe2SiO4 and Pb-Fe2SiO4 in the Raman and XPS results of As-Fe2SiO4. The above calculations determined the similar crystal and electronic structure of Fe2SiO4, in which Cu(II) and Pb(II) with the same valence as Fe(II) replace Fe(II) at the M2 site on Fe2SiO4, while As(III) replaces Fe(II) at the M2 site and also replaces part of Si atoms for charge compensation. This shows that Cu(II), Pb(II) and As(III) tend to replace Fe(II) at the M2 site to produce M-Fe2SiO4 products.
[0052] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for analyzing the heavy metal occupation sites of fayalite phase in smelting slag, characterized in that: The following steps are involved: (1) Silicon dioxide, ferroferric oxide and ferrous sulfide are mixed, mixed by ball milling, smelted, cooled and ball milled to obtain Fe2SiO4 powder; (2) mixing Fe2SiO4 powder with metal oxide, mixing by ball milling, smelting, cooling, crushing and ball milling to obtain M-Fe2SiO4 powder containing heavy metals; (3) Perform XRD analysis and FT-IR analysis on Fe2SiO4 powder and M-Fe2SiO4 powder; (4) Performing Raman analysis and XPS analysis on Fe2SiO4 powder and M-Fe2SiO4 powder; After step (4), DFT calculations are also performed to calculate the occupied sites of heavy metals and fayalite; In step (2), the metal oxide is one or more of copper oxide, lead oxide, and arsenic trioxide, and the M-Fe2SiO4 is one or more of Cu-Fe2SiO4, Pb-Fe2SiO4, and As-Fe2SiO4; The DFT calculation method is as follows: spin-polarized density functional theory calculations are performed using the Hubbard U (DFT+U) correction implemented in the Vienna ab initio Simulation Package, the generalized gradient approximation of Perdew-Burke-Ernzerh is used for electron exchange calculations, the pseudopotential uses a plane wave pseudopotential with a kinetic energy cutoff of 400 eV in the projected augmented wave (PAW) method, and the Hubbard effective U value is set to 3.6 eV to better describe the electrons of Fe 3d, and the energy convergence criterion is set to 10 -5 eV, and continue to optimize the atomic positions until the Hermann-Feynman force on each atom is less than 0.02 eV Å -1 , the Brillouin zone is sampled using a 7 × 3 × 5 k-point grid in the Monkhorst-Pack setup; The XRD scanning angle in step (3) is 20°~60°, and the FT-IR test spectrum range is 4000-400cm -1 ; Step (3) The XRD analysis of the binding relationship between Fe2SiO4 and heavy metals and the FT-IR analysis of the changes in chemical bonds in Fe2SiO4 and M-Fe2SiO4; The Raman analysis and XPS analysis in step (4) determine the occupancy rules of heavy metals in Fe2SiO4.
2. The method according to claim 1, characterized in that The mass ratio of silicon dioxide:ferroferric oxide:ferrous sulfide in step (1) is (7-10): (4-8): (4-8), and the mass of Fe2SiO4 powder in step (2) is 10-20 g.
3. The method according to claim 2, characterized in that The mass ratio of silicon dioxide:ferroferric oxide:ferrous sulfide in step (1) is 7:4:4, the mass of Fe2SiO4 powder in step (2) is 15g, and the amount of metal oxide added is 3.2~11.8 wt% of Fe2SiO4.
4. The method according to any one of claims 1 to 3, characterized in that The ball milling mixing and ball milling conditions in step (1) and step (2) are: ball milling time is 5-10 min, and ball milling speed is 400±100 rpm.
5. The method according to claim 4, characterized in that The particle size of the Fe2SiO4 powder in step (1) and the M-Fe2SiO4 powder in step (2) are both 50-80 mesh.
6. The method according to claim 5, characterized in that The smelting conditions of step (1) and step (2) are: vacuum degree of -0.05~-0.1Mpa, power of 1200~1500W, temperature of 1300~1400℃, time of 10~15min, and natural cooling for 24~36h.